No. 329-Canadian Contraception Consensus Part 4 of 4 Chapter 9: Combined Hormonal Contraception - Black, Amanda; Guilbert, Edith; Costescu, Dustin; Dunn, Sheila; Fisher, William; Kives, Sari; Mirosh, Melissa; Norman, Wendy V.; Pymar, Helen; Reid, Robert; Roy, Geneviève; Varto, Hannah; et al. (Journal of obstetrics and gynaecology Canada, 2017)
To provide guidelines for health care providers on the use of contraceptive methods to prevent pregnancy and on the promotion of healthy sexuality. Overall efficacy of cited contraceptive methods, assessing reduction in pregnancy rate, safety, and side effects; the effect of cited contraceptive methods on sexual health and general well-being; and the availability of cited contraceptive methods in Canada. Medline and the Cochrane Database were searched for articles in English on subjects related to contraception, sexuality, and sexual health from January 1994 to December 2015 in order to update the Canadian Contraception Consensus published February-April 2004. Relevant Canadian government publications and position papers from appropriate health and family planning organizations were also reviewed. The quality of the evidence is rated using the criteria described in the Report of the Canadian Task Force on Preventive Health Care. Recommendations for practice are ranked according to the method described in this report. 1.Although highly effective with perfect use, typical use failure rates for combined hormonal contraceptives, including the combined oral contraceptive pill, are as high as 9% (II-2).2.The majority of qualified studies do not indicate decreased combined oral contraceptive pill efficacy in obese women; however, a small increase in contraceptive failure in women with a body mass index greater than 30 cannot be excluded (II-2).3.Combined oral contraceptive pills are associated with a number of non-contraceptive benefits, including but not limited to decreased menstrual bleeding, decreased acne, fewer endometriosis-related symptoms, and a decreased risk of ovarian and endometrial cancers (II-2).4.Combined oral contraceptive pills (COCs) are associated with an increased risk of venous thromboembolism (II-2). Potential differences in the risk of venous thromboembolism attributable to different progestin types and estrogen dosing in low-dose COCs do not currently justify preferential prescribing (III).5.Low-dose combined oral contraceptive pills (containing less than 50 μg of ethinyl estradiol) are not associated with an increased risk of myocardial infarction or cerebrovascular accident in women with no additional risk factors (II-2).6.Current epidemiological studies suggest that there is no increase in the risk of breast cancer or breast cancer mortality in women who have used combined oral contraceptive pills (COCs) compared with non-users (II-2). There may be a slight increase in breast cancer in current and/or recent COC users (II-2). The use of COCs in BRCA1/2 carriers is controversial but appears to be associated with a decreased risk of ovarian cancer and no increase in the risk of breast cancer (II-2).7.Combined oral contraceptive pills (COCs) are associated with a decreased risk of ovarian, endometrial, and colorectal cancers (II-2). A possible association has been shown between COC use and risk of cervical cancer (II-2), but causation has not been demonstrated.8.A blood pressure measurement is the only examination and/or investigation that is required prior to initiating combined hormonal contraception (CHC) in women who are otherwise healthy by history (II-2). Baseline weight and body mass index assessment might be helpful for monitoring changes in CHC users. Pelvic examination, Pap test, screening for sexually transmitted infections, and thrombophilia screening are not required prior to initiating CHC (III).9.Combined oral contraceptive pills and other combined hormonal contraception (CHC) can be started at any time during the menstrual cycle provided that pregnancy or the possibility of pregnancy can be reasonably ruled out. Where there is uncertainty, the benefits of starting CHC likely outweigh any risks (III).10.Starting combined hormonal contraception immediately (Quick Start) may improve short-term compliance and is not associated with an increase in unscheduled bleeding or other side effects (I).11.The highest risk of ovulation occurs when the hormone-free interval is prolonged for more than 7 days, either by delaying the start of combined hormonal contraception (CHC) or by missing active hormone doses during the first or third weeks of CHC (I). Ovulation rarely occurs after 7 consecutive days of CHC use (II-2).12.Emergency contraception (EC) and back-up contraception may be required in some instances of missed combined hormonal contraception (CHC), particularly when the hormone-free interval has exceeded 7 days. EC is rarely indicated for missed CHC in the second or third week of the cycle unless there are repeated omissions or failure to use back-up contraception after the missed doses (III).13.Combined oral contraceptive pill exposure just prior to or during pregnancy is not associated with an increased risk of major birth defects (II-2).14.The effectiveness of combined hormonal contraception (CHC), including combined oral contraceptive pills, may be affected by other medications, including but not limited to some anticonvulsants, some antiretrovirals, rifampicin, and griseofulvin. CHCs may affect the serum levels of other medications, including some anticonvulsants and antiretrovirals (II-2).15.The contraceptive patch may be less effective in women with a body weight ≥90 kg (II-2).16.Compared with the combined oral contraceptive pill, transdermal contraceptive patch use is associated with less breakthrough bleeding and spotting but more breast discomfort or pain, nausea and vomiting, and dysmenorrhea (I).17.Pharmacokinetic studies indicate that serum hormone concentrations of ethinyl estradiol and norelgestromin are maintained at ovulation inhibitory levels throughout at least 9 days of continuous transdermal contraceptive patch wear (II-2).18.The vaginal contraceptive ring is associated with less unscheduled bleeding than the combined oral contraceptive pill and the duration of menstrual bleeding is significantly shorter than that seen with the contraceptive patch (I).19.Serum levels of ethinyl estradiol and etonorgestrel are maintained at ovulation inhibitory levels for at least 28 days after the vaginal contraceptive ring has been inserted (II-2).20.Continuous and/or extended regimens of combined hormonal contraception (CHCs) have similar rates of adherence and effectiveness compared with 28-day cyclic CHC regimens (I).21.Continuous and/or extended (C/E) regimens of combined hormonal contraception (CHC) are associated with significantly less menstruation-associated symptoms than are cyclic CHC (I). Bleeding and/or spotting with C/E CHC regimens decreases with each successive cycle and is similar to or less than that with cyclic CHC (I). 1.Health care providers should give clear instructions for hormonal contraceptive use, including how to manage missed hormonal contraception, as part of contraceptive counselling. Women should be provided with resources to refer to in the event of missed and/or delayed hormonal contraceptives or if they develop any signs of a serious adverse event while using hormonal contraception (III-A).2.Health care providers should consider advising women who are initiating contraception to start their combined hormonal contraception (CHC) immediately (Quick Start) provided that they are reasonably certain that the woman is not pregnant. Back-up contraception (barrier method) or abstinence should be used for the first 7 consecutive days of CHC use unless CHC was initiated on the first day of menses (I-A).3.Health care providers should consider the possibility of irregular pill taking, concomitant medication use, malabsorption, uterine or cervical pathology, pregnancy, or chlamydial infection in women presenting with persistent unscheduled bleeding on the combined oral contraceptive pill (III-A).4.If 1 combined oral contraceptive pill or other combined hormonal contraception (CHC) method is missed in the first week of use, back-up contraception or abstinence should be used until the CHC method has been used for 7 consecutive days. In the case of missed CHC in the second or third week of hormones, the hormone-free interval should be eliminated for that cycle (III-A).5.Back-up contraception should be used when 3 or more consecutive doses/days of combined hormonal contraception (CHC) have been missed in the second or third week of hormone use until the CHC has been used for 7 consecutive days. For practical reasons, the scheduled hormone-free interval should be eliminated in these cycles (I-A).6.Health care providers should be aware of other medications being used by combined hormonal contraception users and the possibility of drug interactions that could affect serum levels and effectiveness of either medication (II-2A).7.Health care professionals should be aware of the option of using continuous and/or extended combined hormonal contraception regimens and consider offering them to women for contraception, medical reasons, and personal preferences (III-A).8.Women using continuous and/or extended combined hormonal contraception regimens should be counselled about expected bleeding patterns and how to manage unscheduled bleeding or spotting (III-A).9.When a specific product has been prescribed to a woman, she should be informed if a generic substitution is being considered and her health care provider should be advised if a substitution is made. The woman should have the option to agree or disagree to the substitution and be informed about any difference in cost for a specific product (III-B).